Thymoquinone inhibits murine leukemia WEHI-3 cells in vivo and in vitro - Salim, L.Z.A.; Othman, R.; Abdulla, M.A.; Al-Jashamy, K.; Ali, H.M.; Hassandarvish, P.; Dehghan, F.; Ibrahim, M.Y.; Omer, F.A.E.A.; Mohan, S. (Public Library Science, 2014)
Background: Thymoquinone is an active ingredient isolated from Nigella sativa (Black Seed). This study aimed to evaluate the in vitro and in vivo anti-leukemic effects of thymoquinone on WEHI-3 cells. Methodology/Principal Findings: The cytotoxic effect of thymoquinone was assessed using an MTT assay, while the inhibitory effect of thymoquinone on murine WEHI-3 cell growth was due to the induction of apoptosis, as evidenced by chromatin condensation dye, Hoechst 33342 and acridine orange/propidium iodide fluorescent staining. In addition, Annexin V staining for early apoptosis was performed using flowcytometric analysis. Apoptosis was found to be associated with the cell cycle arrest at the S phase. Expression of Bax, Bcl2 and HSP 70 proteins were observed by western blotting. The effects of thymoquinone on BALB/c mice injected with WEHI-3 cells were indicated by the decrease in the body, spleen and liver weights of the animal, as compared to the control. Conclusion: Thymoquinone promoted natural killer cell activities. This compound showed high toxicity against WEHI-3 cell line which was confirmed by an increase of the early apoptosis, followed by up-regulation of the anti-apoptotic protein, Bcl2, and down-regulation of the apoptotic protein, Bax. On the other hand, high reduction of the spleen and liver weight, and significant histopathology study of spleen and liver confirmed that thymoquinone inhibited WEHI-3 growth in the BALB/c mice. Results from this study highlight the potential of thymoquinone to be developed as an anti-leukemic agent.